Empowerment of PKK Groups and Agro Rimba Abadi Forest Farmer Groups through Strengthening the Green Economy to Improve Economy Welfare - Siti Patonah; Hisyam Ma'mun; Ervina Eka Subekti; Eka Adi Supriyanto (Universitas Lambung Mangkurat, 2026)
The implementation of the green economy requires massive and sustainable training and workshops. The purpose of this activity is to provide integrative training in implementing the green economy in rural areas for the PKK group and the Agro Rimba Abadi forest farmer group. The method used is participatory action research (PAR). Participants are involved in all activities, including collecting data on the necessary training needs and following up on activities after participating in the training. There are 4 training themes, namely: pineapple cultivation, designing products suitable for sale, business licenses, and e-commerce. The results obtained were: increased understanding of partners consisted of 3 groups, namely: experiencing an increase, not experiencing change, and experiencing a decrease. A total of 67% of participants had an increased understanding of the theme of